IMPLIKASI DUALISME KEWENANGAN PENYIDIKAN TINDAK PIDANA KORUPSI ANTARA KEPOLISIAN, KEJAKSAAN DAN KPK - Dwi Oktafia Ariyanti (Kajian Hasil Penelitian Hukum, 2018)
National legal system is not only consisted of law rules or norms, but also includes the whole apparatus of institutions and organizations, mechanisms and legal procedures, philosophy and culture of law including law behavior of the government and society.In efforts to against corruption, have to be realized that it was done within the framework of national legal systems, structured and organized. There are three institutions which have the authority to investigate corruption cases, namely police, prosecutors, and the Corruption Eradication Commission. The authority of each institution has been managed in its own law products, so it will no longer overlap in executing the corruption investigations.This research was conducted using normative juridical approach, this study has a descriptive form. The data used is secondary data because it focuses on the study of literature, data collections were taken by reviewing the literature and study cases. Results of this study concluded that the realization of harmony between police, prosecutors and the Corruption Eradication Commission (KPK) in investigating the corruption cases must coordinate to each institutions of corruption investigation comity. Beside coordination, agreements are also important to avoid negative rivalry amongst these institutions. If this important thing is not immediately resolved, agenda of corruption eradication will not be done well.